Natyoshala : all the world is a stage (2008)
[Dt.:] Natyoshala ist eine bengalische Theatergruppe aus Chicago, die auf ihrer Webseite neben Informationen zu ihren eigenen Produktionen auch Filmausschnitte, Audiostreams und ganze Dramentexte anbietet. - [Engl.:] Natyoshala is Bengali theatre group from Chicago, USA. It provides information on the different productions of the group and contains videos of their work, audiostreams and whole drama scripts.